The management of mesh complications. Issue 11 (November 2022) - Abbas, Nazish; Reid, Fiona
Abstract: Polypropylene mesh has been widely used in Urogynaecology for the management of prolapse and stress urinary incontinence. Growing recognition of long-term complications has led to the pause on all vaginally inserted mesh within the UK and other countries. These complications include vaginal mesh exposure, visceral perforation and chronic pain. It is important for all gynaecologists to be aware of these complications, signs, assessment and possible management options. Ultimately, a regional mesh centre should be involved in the care of these women as management if often complex. This article discusses different types of mesh, possible clinical presentations and the investigations which may be offered. Management options are outlined, however, involvement of the multidisciplinary team to provide adequate management options is essential.